2020
DOI: 10.3389/fonc.2019.01528
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Burden in Elderly Patients With Localized Prostate Cancer Treated With Stereotactic Body Radiation Therapy (SBRT)

Abstract: Retaining quality of life in patients treated with SBRT for prostate cancer remains paramount. As such, balancing the benefits of treatment against the effects of therapy on elderly patients is essential. The EORTC QLQ-ELD14 (ELD-14) is a validated questionnaire with a domain dedicated to burden of illness and treatment in the elderly. The Expanded Prostate Cancer Index Composite (EPIC)-26 is a validated questionnaire which measures urinary, bowel, sexual, and hormonal symptoms. This study reports trends in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The consistent results of these studies, most of which are getting old and use 3D, suggest a legitimate benefit in treating elderly patients with radical radiotherapy. This is even truer now, particularly with the advent of new techniques such as IMRT or stereotactic body radiation therapy (SBRT) that allow dose escalation [29] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The consistent results of these studies, most of which are getting old and use 3D, suggest a legitimate benefit in treating elderly patients with radical radiotherapy. This is even truer now, particularly with the advent of new techniques such as IMRT or stereotactic body radiation therapy (SBRT) that allow dose escalation [29] .…”
Section: Resultsmentioning
confidence: 99%
“…Nguyen et al reported the outcomes of 206 pts (MA 72.4y), with intermediate to high-risk PC treated with EBRT (70 Gy) vs EBRT + ADT (6 months) [29] . The authors showed a significant decrease in 8-year mortality with ADT (16.5% vs 41.4%) in the elderly with no/mild comorbidities but a deleterious effect in those who presented moderate/severe comorbidities [36] .…”
Section: Resultsmentioning
confidence: 99%
“…A recent article by Aghdam et al. [29] reported trends in self‐reported burden (ELD14) in a sample of 111 patients aged >70 years with PCa treated with stereotactic body RT between start of the treatment and 24 months. During this time period, they observed an average change of −5.6 units in a total ELD‐14 burden score (burden of treatment and illness).…”
Section: Methodsmentioning
confidence: 99%
“…It can be assumed that at the time of the evaluation at 36 months, there are negligible treatmentrelated mortality differences between the arms, and thus any missing values in HRQoL scores caused by death are equally distributed across the arms. A recent article by Aghdam et al [29] reported trends in self-reported burden (ELD14) in a sample of 111 patients aged >70 years with PCa treated with stereotactic body RT between start of the treatment and 24 months. During this time period, they observed an average change of À5.6 units in a total ELD-14 burden score (burden of treatment and illness).…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…Treatment is well-tolerated and toxicity is low even in elderly patients [ 3 - 4 ]. Testicular scatter results in small (10%-30%) transient testosterone declines that do not impact fatigue or sexual function [ 5 - 6 ].…”
Section: Introductionmentioning
confidence: 99%